Clinical pharmacokinetics and pharmacodynamics of vildagliptin 50 mg sustained release tablet formulation in healthy Indian males after single and multiple-dose - Pote, Alok; Ravisankar, Santhanam; Sangle, Ganesh; Agarwal, Sunil; Patil, Mohan; Deshmukh, Nitin; Kale, Sushil; Baig, M.L.A.; Yarramshetti, Viresh; Debnath, Khokan; Shah, Ruchi; Ingole, Shahu; et al. (International Journal of Research in Medical Sciences, 2021)
Background: Vildagliptin 50 mg once-daily is a clinically established anti-diabetic therapy in combination with a sulphonylurea and renally impaired patients. We developed sustained release (SR) vildagliptin 50 mg tablet formulation for prolongation of dipeptidyl peptidase-4 (DPP-4) inhibition coverage. The present study compares the pharmacokinetic (PK) and pharmacodynamic (PD) characteristics of investigational vildagliptin SR 50 mg tablet with Galvus® in healthy Indian adult males after single and multiple-dose administration. Methods: Each randomized, open-label, two-period, cross-over study enrolled 36 healthy Indian adult male subjects for the assessment of single and multiple-dose PK/PD profiles of SR 50 mg vildagliptin under fed condition. The plasma drug concentrations were quantified using a validated liquid chromatography-tandem mass spectrometry (LC-MS/MS) method. PK parameters (Cmax (ng/ml), AUC0-18, AUC0-36, and AUC0-τ (ng.hr/ml), Tmax (hour), t1/2 (hour), Tmaxss (hour), Cτss (ng.hr/ml) were calculated using Phoenix® WinNonlin® software. The DPP-4 inhibition was determined in a fluorescence-based assay. Results: Vildagliptin SR tablet showed prolonged PK/PD characters compared to Galvus®. All PK parameters expressed as Mean±SD. The single-dose PK measures were Cmax (58.22±11.31), AUC0-18 (556.92±135.84), AUC0-36 (608.82±159.84), Tmax (6.48±3.78). In the multiple-dose study, PK findings were Cmax (73.20±17.71), AUC0-τ (714.36±303.21), Cτss (4.15±6.51), Tmaxss (5.60±3.12). Vildagliptin SR 50 mg achieved prolonged DPP-4 inhibition (≥80%) for18-20 hours after single and multiple-dose administration as compared to Galvus® (12-13 hours). Conclusions: Investigational vildagliptin SR tablet was found safe, well-tolerated after single and multiple-dose administration. Its extended DPP-4 inhibition profile compared to Galvus® may benefit the patient population on combination therapy with a sulphonylurea and renally impaired patients.